Key trends in public agricultural research capacity and investments in Central America - Stads, Gert-Jan (International Food Policy Research Institute, 2008)
This brief provides an overview of the major investment trends in agricultural research in Central America since the early 1980s, drawing on a new set of data developed through a comprehensive survey by the International Food Policy Research Institute (IFPRI) and the Inter-American Institute for Cooperation on Agriculture (IICA).